Gestão Integrada de Bacias Hidrográficas: paisagem cultural e parques fluviais como instrumentos de desenvolvimento regional - André Munhoz de Argollo Ferrão; Luci Mehry Martins Braga (Confins)
Human interventions confer personality and characteristics to certain regions. This interaction resulting cultural landscapes relevant asset value that mark the work of man over the territory. The revitalization of these special places is a recurring phenomenon in many parts of the world, impacting positively on the recovery processes of the rivers that cross such territories and that confer identity to the corresponding landscape. This article comes to associate the idea of ​​Parks River and the cultural landscape as instruments of regional development within the programs of integrated river basin management.